Adverse effects of isotretinoin: A large, retrospective review. Issue 4 (14th March 2017) - Brzezinski, Piotr; Borowska, Katarzyna; Chiriac, Anca; Smigielski, Janusz
Abstract: Acne is a very common and disfiguring disease that affects mostly adolescents and, to some extent, adults. The objective of our study was to estimate the adverse effects after isotretinoin by treatment of 3, 525 patients due to acne vulgaris in a 5‐year observation. Retrospective, comparative study was carried out in Poland and Romania from January 2012 to August 2016. Inclusion criteria into this study were moderate, severe, and nodulocystic inflammatory acne vulgaris. Exclusion criteria were mild acne, pregnant, and lactating women. Statistical analysis was carried out using T test and Chi square. All patients were treated with oral isotretinoin. Patient age ranged from 13‐35 years. Dry lips was the most commonly reported adverse effect, affecting 100% of users, followed by xerosis (94.97%) and facial erythema (66.21%). Of all adverse effects, psychiatric symptoms accounted for 25.16%; eye lesions accounted for 8.96%. In lab investigations an increase in the level of total cholesterol and serum triglycerides was observed. This study documents the adverse effect profile of isotretinoin in a large number of patients collected over a period of 4 years. Side effects were mild and well tolerated and did not necessitate stopping the treatment. However, it is important to educate patients about this potential consequence.